Pelatihan Pengenalan Media Flash Dan Aplikasi Paint Untuk Meningkatkan Kemampuan Berbahasa Pada Anak Usia Dini Dan Taman Kanak-Kanak Sekolah TK Swasta Tridaya Mandiri Bandar Setia Percut Sei Tuan - Erma, Ermayanti Astuti; Nurhayati; Savira Ramadhani (Publikasi Pengabdian Masyarakat, 2023)
ABSTRACT Tridaya Mandiri Private Kindergarten Bandar Setia Percut Sei Tuan Deli Serdang is one of the national standard schools in the world of early childhood education and kindergartens which are required to always develop and improve the quality of education and professionalism of service to students. Today's Information and Communication Technology (ICT) is really needed by students, especially the introduction of drawing application media to students at Tridaya Mandiri Percut Sei Tuan Private Kindergarten. Training on the introduction of paint application is urgently needed as a medium for information and communication technology so that later students can use it properly. Students cannot fully use the Paint application, especially materials related to Paint and Media Flash, because schools are not taught and the high cost of computer courses among students in the area around Percut Sei Tuan Deli Serdang, especially in Bandar Setia. One way is to practice the introduction of skills using the painting and drawing application with the Microsoft Paint application. Community service activities are emphasized in the form of training on how to introduce and apply Microsoft Paint for students. Tridaya Mandiri Private Kindergarten Bandar Setia Percut Sei Tuan Deli Serdang with a total of 22 students. It is hoped that with this introductory training, students will be able to know more about drawing and painting techniques with computer media on using Microsoft Pain, by utilizing Microsoft Paint from the community service activities carried out to provide experience and skills for students and students in using Microsoft Paint. Thus, the implementation of community service activities at Tridaya Mandiri Private School Kindergarten Bandar Setia Percut Sei Tuan Deli Serdang. Introducing and using Microsoft Paint provides significant benefits for improving the skills of students in utilizing computer information technology for drawing and painting facilities, they are very enthusiastic about participating in this activity to completion. . Keywords : Tridaya Mandiri Kindergarten, Training, Microsoft Paint, Flash Media, Early Childhood and Kindergarten Language Skills.